2009
DOI: 10.1007/s11104-009-0055-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of single chemical extractants for the prediction of heavy metal uptake by barley in soils amended with polluted sewage sludge

Abstract: The main aim of this study was to compare the suitability of three single chemical extractants [EDTA, CaCl 2 and the low-molecular-weight organic acids solution (LMWOAs)] to estimate Cu, Zn and Ni uptake by barley (Hordeum vulgare) from rhizosphere soils, following a single application of a metal saltsspiked sewage sludge. Thirty-six contrasting soils from different parts of Spain were amended with the same dose (15.71 g dry weight kg -1 ) of polluted sewage sludge and sown with barley seeds under greenhouse c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 62 publications
4
16
0
Order By: Relevance
“…However, other studies (e.g., [84]) showed that extracting agents such as EDTA can not be used as universal soil extraction for estimating Cu, Zn, and Ni uptake by barley. Peijnenburg et al [85] made an overview of empirical methods for extraction of metals from soils as a surrogate for bioavailable and bioaccessible metal pools.…”
Section: Relation Between Edta Extractablementioning
confidence: 99%
“…However, other studies (e.g., [84]) showed that extracting agents such as EDTA can not be used as universal soil extraction for estimating Cu, Zn, and Ni uptake by barley. Peijnenburg et al [85] made an overview of empirical methods for extraction of metals from soils as a surrogate for bioavailable and bioaccessible metal pools.…”
Section: Relation Between Edta Extractablementioning
confidence: 99%
“…McBride et al (2003) recommend diluted CaCl 2 as a universal extractant for assessment of the availability of trace metals to plants. Soriano-Disla et al (2010) demonstrated that solution of low-molecular-weight organic acids can be used as a universal extractant to foresee the uptake of copper (Cu), Zn, and Ni by barley.…”
Section: Introductionmentioning
confidence: 99%
“…Both single and sequential extraction procedures have been used to estimate the distribution and availability of Cu in soils ( Guan et al, 2011). The single extraction is convenient to perform ( Soriano‐Disla et al, 2010), but the sequential extraction technique provides more detailed information on Cu fractionation as well as the actual and potential transport of different chemical forms ( Tessier et al, 1979; Doelsch et al, 2008). In soil matrix, Cu can be associated with soil components and exist in various chemical and physical forms including soluble and exchangeable Cu, Cu precipitated with iron and manganese oxides or carbonates, Cu complexes with or adsorbed to organic matter, and Cu associated with clay minerals ( Ahumada et al, 2009).…”
Section: Introductionmentioning
confidence: 99%